Purpose‐built national burns center: The Israeli experience. (22nd January 2018) - Ofir, Hagit; Shefler, Hadas; Kornhaber, Rachel; Cleary, Michelle; Harats, Moti; Haik, Josef
Abstract: The opening of the National Burns Center (NBC) in Sheba Medical Center (SMC) in 2014 was a keystone point in the development of specialized burns trauma services for Israel to ensure burn care and disaster planning at international standards. The NBC is a purpose‐built, level 1 burns trauma center that receives patients from Israel, Gaza, West Bank, and abroad. Hosting six intensive care and four step‐down burns beds, the center serves as a referral center for patients in other health‐care facilities with indication for hospitalization. In the present study, we describe the planning, design, and organization of the NBC at the SMC with reference to some of the key areas and considerations in its conception and development. With the improved survival rates of patients with extensive burns and the demographics and characteristics among burn‐injury patients in Israel, the NBC has the capacity to be the center of excellence in burns care, teaching, and research within the Middle East.